Formas de apresentação do milho em rações de frangos de corte, dos 22 aos 42 dias de idade, sem ou com a presença de pedrisco - Silva Júnior, Veredino Louzada da (2002)
In order to verify the influence of non-processing or processing forms of corn and the presence of granitic grit on the performance, carcass and gizzard development in broiler chickens,720 birds of both sexes were used. Chickens were submitted to the following treatments: processing form (whole, gross and fine ground), grit (absence and presence) and sex (male and female). Isonutritive diets with 19.1% of CP and 3,033 Kcal of ME/kg, were used. A completely randomized design in 3 x 2 x 2 factorial scheme (processing form, presence and absence of grit and sex), with four replicates and fifteen bird seach. A total of three consecutive periods (22 to 28, 29 to 35 and 36 to 42 days) were used as subplots. From 22 to 42 days, broilers in no grit diets reduced (P<0,05) feed intake with fine ground corn in relation to the ones receiving grit. However, grit did not influence feed intake of birds fed whole or gross ground corn rations. No effect (P>0,05) of grit was observed with relation to the other performance traits. Apparently, no advantages were obtained with grit inclusion, since it did not benefit either performance or carcass yield. Grit absence or presence did not affect (P>0,05) empty gizzard weight. Highest (P<0,05) weight gain and feed conversion were obtained in birds fed ground cora (gross or fine) diets. Non processing or different processing forms did not affect (P>0,05) carcass yield; but whole corn diet increased (P<0,05) fat pad content. Gizzards developed more (P<0,05) with the use of whole corn ration. Grit intake was not influenced (P>0,05) by treatment. In conclusion, the use of gross ground corn by 21day-old Broilers may be feasible. Whole corn reduced performance, increased fat pad content and gizzard development. Grit did not present any advantage.